The Teaching Methods and Techniques Of The Prophet (PBUH): An Exploratory Study - Taofeek Muhammed Thani; Ibrahim Dahiru Idriss; Adamu Abubakar Muhammad; Hafsat Sulaiman Idris (USIM Press, 2024)
Vol 6. No. 1 (June 2021)